EFEKTIVITAS METODE DISKUSI DALAM KETERAMPILAN BERBICARA TEKS PIDATO PADA SISWA KELAS IX SMP NEGERI I PANGURURAN TAHUN 2021 - Esra Perangin-angin; Elivirida Sitanggang; Medi Anryani Sianipar; Rati Yohana Sibarani (Universitas Islam Sumatera Utara, 2022)
. The purpose of this study is to determine the effectiveness of the speaking skills of the class IX students of SMP Negeri Pangururan Pangururan District, Samosir Regency in the 2021/2022 academic year through the use of the discussion method. The type of this research used a quantitative research with a sample of 28 students in class IX SMP Negeri 1 Pangururan. The data collection technique used in this study is a test technique, namely pretest and posttest. The analyzed of this data using statistical data analysis techniques. The effectiveness of students' speaking skills can be seen from the increase in student scores at the pretest and posttest stages. The average pretest score of students before being given treatment was 49.1, after being given treatment at the end of the post-test the average was 80.75. This shows the effectiveness in speaking skills.